Dust deposition on the decks of the Mars Exploration Rovers: 10 years of dust dynamics on the Panoramic Camera calibration targets. Issue 5 (23rd May 2015) - Kinch, Kjartan M.; Bell, James F.; Goetz, Walter; Johnson, Jeffrey R.; Joseph, Jonathan; Madsen, Morten Bo; Sohl‐Dickstein, Jascha
Abstract The Panoramic Cameras on NASA's Mars Exploration Rovers have each returned more than 17, 000 images of their calibration targets. In order to make optimal use of this data set for reflectance calibration, a correction must be made for the presence of air fall dust. Here we present an improved dust correction procedure based on a two‐layer scattering model, and we present a dust reflectance spectrum derived from long‐term trends in the data set. The dust on the calibration targets appears brighter than dusty areas of the Martian surface. We derive detailed histories of dust deposition and removal revealing two distinct environments: At the Spirit landing site, half the year is dominated by dust deposition, the other half by dust removal, usually in brief, sharp events. At the Opportunity landing site the Martian year has a semiannual dust cycle with dust removal happening gradually throughout two removal seasons each year. The highest observed optical depth of settled dust on the calibration target is 1.5 on Spirit and 1.1 on Opportunity (at 601 nm). We derive a general prediction for dust deposition rates of 0.004 ± 0.001 in units of surface optical depth deposited per sol (Martian solar day) per unit atmospheric optical depth. We expect this procedure to lead to improved reflectance‐calibration of the Panoramic Camera data set. In addition, it is easily adapted to similar data sets from other missions in order to deliver improved reflectance calibration as well as data on dust reflectance properties and deposition and removal history.